Upaya Meningkatkan Hasil Belajar Matematika Materi Persamaan Kuadrat Melalui Model Discovery Learning Pada Siswa Kelas IX C SMP Negeri 13 Magelang Tahun Pelajaran 2022/2023 - Jumono, Jumono (Science and Education Journal (SICEDU), 2024)
This research aims to: 1) Describe the process of implementing the discovery learning model in improving mathematics learning outcomes regarding quadratic equations in class IX C students at SMP Negeri 13 Magelang. 2) Describe the level of mathematics learning outcomes in quadratic equation material on the subject after implementing the discovery learning model. This research is classroom action research, which consists of two cycles, each cycle consisting of three stages of activities, namely; planning, action and observation, and reflection. The research subjects were 32 students in class IX C at SMP Negeri 13 Magelang. Data collection in this research used observation sheets and learning outcome assessment sheets. The data analysis techniques used are qualitative descriptive and quantitative descriptive. Based on the results of the research and discussion, data obtained on the increase in learning outcomes for Quadratic Equations in class IX C students of SMP Negeri 13 Magelang after implementing learning with Discovery Learning in the first cycle was an average of 73.03 with a completion percentage of 78.13% after carrying out the second cycle as a whole. The average is 75.63 with a learning completion percentage of 87.5%. These results show that the Discovery Learning model can improve the learning outcomes of class IX C students at SMP Negeri 13 Magelang for the 2022/2023 academic year.